Energy transfer and frequency upconversion in Yb3+-Er3+-doped PbO-GeO2 glass containing silver nanoparticles - Kassab, L. R P [UNESP]; Bomfim, F. A.; Martinelli, J. R.; Wetter, N. U.; Neto, J. J.; Araujo, Cid B. de (Springer, 2009)
We report the infrared-to-visible frequency upconversion in Er3+-Yb3+-codoped PbO-GeO2 glass containing silver nanoparticles (NPs). The optical excitation is made with a laser at 980 nm in resonance with the F-2(5/2)-> F-2(7/2) transition of Yb3+ ions. Intense emission bands centered at 525, 550, and 662 nm were observed corresponding to Er3+ transitions. The simultaneous influence of the Yb3+-> Er3+ energy transfer and the contribution of the intensified local field effect due to the silver NPs give origin to the enhancement of the whole frequency upconversion spectra.